2007
DOI: 10.1086/513604
|View full text |Cite
|
Sign up to set email alerts
|

A Narrow-Line Seyfert 1-Blazar Composite Nucleus in 2MASX J0324+3410

Abstract: We report the identification of 2MASX J032441.19ϩ341045.9 (hereafter 2MASX J0324ϩ3410) with an appealing object that shows the dual properties of both a narrow-line Seyfert 1 galaxy (NLS1) and a blazar. Its optical spectrum, which has a Hb line width of about 1600 km s Ϫ1 (FWHM), an [O iii]-to-Hb line ratio of Ӎ0.12, and strong Fe ii emission, clearly fulfills the conventional definition of NLS1s. On the other hand, 2MASX J0324ϩ3410 also exhibits some behavior that is characteristic of blazars, including a fla… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
193
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(211 citation statements)
references
References 38 publications
17
193
1
Order By: Relevance
“…3 we showed that PKS 2004−447 exhibits radio flux density variability up to a factor of 2 on time scales of months to years at centimetre wavelengths, which are comparable to values reported for other γ-NLS1s (e.g., Zhou et al 2007;D'Ammando et al 2013a,b;Angelakis et al 2015). The recent studies by Foschini et al (2015) and Angelakis et al (2015) have presented the densest, simultaneous multi-frequency radio monitoring of four γ-NLS1s.…”
Section: Flux Density Variability and Spectrumsupporting
confidence: 85%
“…3 we showed that PKS 2004−447 exhibits radio flux density variability up to a factor of 2 on time scales of months to years at centimetre wavelengths, which are comparable to values reported for other γ-NLS1s (e.g., Zhou et al 2007;D'Ammando et al 2013a,b;Angelakis et al 2015). The recent studies by Foschini et al (2015) and Angelakis et al (2015) have presented the densest, simultaneous multi-frequency radio monitoring of four γ-NLS1s.…”
Section: Flux Density Variability and Spectrumsupporting
confidence: 85%
“…For 1H 0323+342, Hubble Space Telescope images show a ring-like structure (Zhou et al 2007). More detailed studies of the host galaxy decompose into several components, (1) a core, (2) a disk, and (3) a ring, displaying evidence for a recent galaxy interaction rather than secular evolution (León Tavares et al 2014).…”
Section: Host Galaxymentioning
confidence: 99%
“…(3) The radio-loudness of 1H 0323 +342 is high, indicating that the relativistic jet is beamed. (4) Its extensively studied host galaxy shows a complicated structure (e.g., Zhou et al 2007;León Tavares et al 2014), which is different from the paradigm of giant elliptical galaxies as hosts of radio-loud active galactic nuclei (AGNs) (e.g., Scarpa et al 2000). The key point to understand these issues is to measure the black hole mass through reverberation mapping.…”
mentioning
confidence: 99%
“…Furthermore, in general the host galaxies of radio-loud NLS1 have not been yet well characterised and, therefore, it is not clear that these object are host by disk galaxies. Two examples (see Zhou et al 2007;Foschini 2011) suggest that this could be the case at least for some of them. If this is confirmed for a larger sample, it may indicate a possible, interesting link between this group of object and objects like PKS 1814-637.…”
Section: Link To Seyfert Galaxiesmentioning
confidence: 99%